Efektivitas Koordinasi antar Stakeholders Penanggulangan Bencana oleh Badan Penanggulangan Bencana Daerah (BPBD) Kota Padang - Nesy Yulia Murni; Zikri Alhadi (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2019)
This study aims to determine the effectiveness of the performance of the Padang Disaster Management Agency in coordinating among stakeholders in disaster management in the city of Padang. The research method used in this study is qualitative research. Data collection techniques in this study were conducted by interview and documentation study. The research was conducted at the Padang Disaster Management Agency (BPBD) office, Padang Social Service office, Padang Search and Relief Agency office, and Padang Red Cross (PMI) Headquarters. The technique of selecting informants that the researchers used was purposive sampling. The results of the study showed that the function of coordination carried out by the BPBD of Padang City could be said to be effective. This is because all stakeholders are involved in handling disasters, especially during emergency response. Among the forms of coordination is the involvement of the Rapid Reaction Team (TRC) which plays a role in identifying disaster status so that handling can be quickly carried out. Furthermore BPBD along with relevant stakeholders also coordinated to carry out joint handling in providing assistance to disaster victims.